Gas porosity defect – what it means and how to respond - Sheladiyaa, Manojkumar V.; Acharya, Shailee G.; Acharya, Ghanshyam D. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The foundries are facing problem-related to the selection of the parameter’s value for minimum rejection and maximum productivity. The furan no-bake binders system guaranteed dimensional stability and a comparative good surface finish of the casting. Based on past data in the industry, it is found that gas porosity defect is one of the highest. The phenomenon of the formation of the bubble in the fissures of the mould-metal interface, and later on trapping during the solidification leads to gas porosity. The current research work is focused on the minimization of the defect by the selection of the optimum range of input variables. Based on rigorous literature survey and industrial expert’s opinion, it is found that the parameters like grain fineness number (GFN) of the sand, loss on ignition (LoI) of the used sand, the sand temperature at the mixing time, potential of hydrogen (pH) are important parameters for gas porosity defect in the casting.Design-Expert software and particularly response surface methodology (RSM) and sequential approach using the face-centered central composite design is used for the experiments. The results show that a quadratic model with the removal of some insignificant term is a comparatively best fit for gas porosity defects. After analysis, various favorable levels of different parameters are obtained. The research work is based on realistic problems of the foundries and based on the experimental work. Thus, the provided solution is very much useful for foundries to reduce the rejection, particularly for furan no-bake with furfuryl alcohol as resin and sulphonic acid as catalyst. The research problem addressed in the paper is a genuine problem of the foundries and the sole work is based on experimental evidence.